The EFFECT OF EMOTIONAL MARKETING AND LIFESTYLE ON CUSTOMERS DECISIONS IN PRODUCTS CHOOSING OF MURABAHAH FINANCING AT PT BANK SYARIAH MANDIRI KC PALEMBANG SIMPANG PATAL - Cepaldo Cepaldo; Rika Lidyah Rika; Ariyanti Ariyanti (Journal of Business Studies and Management Review, 2020)
The purpose of this research is to analyze and know how the influence of emotional marketing and lifestyle on customers decisions in choosing products of murabahah financing at PT Bank Syariah Mandiri KC Palembang Simpang Patal in partial and simultan. This research study is ( explanatory research ) using a quantitative approach. Source of data in this research use the primary data through questionnaire .The sample collection technique used is a method of purposive sampling, with the multiple regression analysis methods included in this research is 100 respondents who use murabahah financing at PT Bank Syariah Mandiri KC Palembang Simpang Patal. In this research data analysis techniques used SPSS 17.0 version. The research variables consist of the independent variable: 1.emotional marketing 2.lifestyle and the independent variable used the customers .The result show the research indicated that the emotional marketing and lifestyle significantly influence on customers decisions in choosing of the murabahah financing at PT Bank Syariah Mandiri KC Palembang Simpang patal.